(untitled) (Research, Society and Development, 2022)
The previous nutritional status of individuals with end-stage renal disease has an important impact on the outcomes of Kidney Transplantation. Thus, the study aimed to characterize factors relevant to nutritional status in pre-kidney transplant patients at a referral hospital in Fortaleza-CE. Is characterized as a Cross-sectional, descriptive and retrospective study consisting of 136 patients aged over 18 years of both sexes admitted to undergo Kidney Transplantation from March 2018 to March 2020. Clinical, biochemical and anthropometric data were collected. Statistical analyzes were performed using Statistical Product and Service Solutions - SPSS® (version 20) software. Data were transmitted by Fisher’s exact, chi-square (χ2), Kolmogorov-Smirnov, Student’s t, Mann-Whitney tests. Significance level was set at p <0.05. There was an association between age and Body Mass Index (BMI). It was found that the elderly (≥ 60 years) had a higher odds ratio of having a BMI <18.5 kg / m² (p < 0.031). According to biochemical data, most of the sample has nutritional impairment according to Total Lymphocyte Count (TLC) and lymphocyte/monocyte ratio. It was found that patients aged ≥60 years of age had a lower mean lymphocyte/monocyte ratio when compared to patients aged <60 years. As for the comorbidities evaluated, Systemic Arterial Hypertension (SAH) was the most prevalent in the sample. Elderly people are more susceptible to nutritional impairment. Given the various factors that contribute to this condition, the clinical and nutritional assessment and monitoring of these patients is of great importance.